A statistical comparison of silver and SYPRO Ruby staining for proteomic analysis. - White, I; Pickford, R; Wood, J; Skehel, J; Gangadharan, B; Cutler, P (Wiley, 2004)
Silver staining has been the method most commonly employed for high sensitivity staining of proteins following two-dimensional gel electrophoresis. Whilst this method offers detection in the nanogram range it does have major drawbacks including a lack of linearity, nonstoichiometric staining of proteins, a lack of compatibility with the microchemical preparation of proteins for identification by mass spectrometric techniques, and a highly subjective assessment of the staining endpoint. SYPRO Ruby is a relatively new, ruthenium complex-based stain which is reported to offer advantages over silver, particularly in overcoming the limitations cited above. We describe a series of experiments where several protein staining procedures commonly employed are compared. To enable optimization of the in situ digestion procedure, a statistical approach has been undertaken. The effects of a variety of staining, digestion, and analysis protocols on the downstream processing of a test radiolabeled protein were studied. The data confirms that as well as offering sensitivity similar to silver, SYPRO Ruby staining is reproducible, linear, and offers a higher level of compatibility with the identification of proteins by mass spectrometry.